Elective neck irradiation versus observation in squamous cell carcinoma of the maxillary sinus with N0 neck: A meta‐analysis and review of the literature. Issue 12 (1st August 2014) - Abu‐Ghanem, Sara; Horowitz, Gilad; Abergel, Avraham; Yehuda, Moshe; Gutfeld, Orit; Carmel, Narin‐Nard; Fliss, Dan M.
Abstract: Background: Elective neck irradiation of a clinical node‐negative (N0) neck in squamous cell carcinoma (SCC) of the maxillary sinus is a controversial issue. Methods: A systematic review of electronic databases and a meta‐analysis were conducted to clarify the role of elective neck irradiation in patients with SCC of the maxillary sinus and clinical N0 neck. Regional (neck) nodal recurrence was chosen as the primary endpoint. Results: Four retrospective studies with a total of 129 patients met the inclusion criteria. The results of the meta‐analysis showed that elective neck irradiation reduced the risk of regional nodal recurrence (fixed effects model: odds ratio [OR] = 0.16; 95% confidence interval [CI] = 0.04–0.67; p = .01; random‐effects model: OR = 0.17; 95% CI = 0.04–0.76; p = .02) compared to observation. Conclusion: This systemic review and first meta‐analysis confirmed that elective neck irradiation can significantly reduce the rate of nodal recurrence in patients with N0 SCC of the maxillary sinus. © 2014 Wiley Periodicals, Inc. Head Neck 37: 1823–1828, 2015